O040 Associations between Sleep Irregularity and Hypertension: Sleep Sensor Data from Over Two Million Nights. (9th November 2022) - Scott, H; Lechat, B; Reynolds, A; Lovato, N; Escourrou, P; Catcheside, P; Eckert, D
Abstract: Introduction: Irregular sleep has been associated with worse cardio-metabolic health compared to regular sleep, but prior studies are limited in sample size and have assessed sleep irregularity over short assessment periods (7-14 days). This study investigated associations between sleep irregularity and hypertension in a large, global sample over multiple months. Methods: Data from 12, 300 participants (Mean ± SD; 50 ± 12 years, 12% females) who used an under-mattress sleep device and a portable blood pressure monitor between July 2020 and March 2021 were included. Each participant had ~180 nights of recordings and ~70 blood pressure entries. Sleep duration regularity was assessed as the standard deviation of device-assessed total sleep time. Sleep timing regularity was assessed as the standard deviation of sleep onset time and sleep midpoint. Logistic regressions were conducted, controlling for age, sex, BMI, and mean total sleep time. Results: Across total sleep time quartiles, sleep duration irregularity was consistently associated with a 9-15% increase in hypertension risk. A 38-minute increase in sleep midpoint irregularity was associated with an 11% (1.11 [1.03, 1.20]) increase in hypertension risk, independent of mean total sleep time and mean sleep midpoint. Similarly, a ~31-minute increase in sleep onset time irregularity was associated with a 29% increased risk of hypertension (1.29 [1.18, 1.42]). Conclusions: Irregular sleep, regardless of average total sleep time, was associated with increased hypertension risk. Further assessment of day-to-day fluctuations in sleep duration and timing for potential effects on next-day blood pressure and cardiovascular health outcomes is warranted.